2011
DOI: 10.1002/rcm.4913
|View full text |Cite
|
Sign up to set email alerts
|

Mild route to generate gaseous metal anions

Abstract: Gaseous metal anions such as Na(-), K(-), Cs(-), and Ag(-) can be generated at ambient temperatures by the collision-induced dissociation of the anions of several dicarboxylic acid salts, including oxalate, maleate, fumarate, succinate, and glutamate salts. The formation of gaseous metal anions in this way is unprecedented because the metal is initially present in its cationic form. The mild process described here could facilitate novel applications of metal anions as selective reagents for gas-phase ion-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…These complexes are formed by electrospraying a solution of oxalic acid and a Mg 2+ salt (MgX 2 , X = Cl, Br). [8] The mass spectra show that the X = OH complex is reactive in S N 2 gas phase reactions, providing support for the bidentate [HOMg(h 2 -O 2 C)] À structure analogous to structure 1 in Figure 1. However, the G4-level calculations included in that paper [8c] suggest the presence of an additional isomer [HOMg(h 2 -CO 2 )] À with the more classic structure (B), analogous to structure 2 in Figure 1, which is 32 kJ mol À1 higher in energy than 1.…”
mentioning
confidence: 73%
“…These complexes are formed by electrospraying a solution of oxalic acid and a Mg 2+ salt (MgX 2 , X = Cl, Br). [8] The mass spectra show that the X = OH complex is reactive in S N 2 gas phase reactions, providing support for the bidentate [HOMg(h 2 -O 2 C)] À structure analogous to structure 1 in Figure 1. However, the G4-level calculations included in that paper [8c] suggest the presence of an additional isomer [HOMg(h 2 -CO 2 )] À with the more classic structure (B), analogous to structure 2 in Figure 1, which is 32 kJ mol À1 higher in energy than 1.…”
mentioning
confidence: 73%
“…The factor of improvement spans from 1.2 to 17 in positive‐ion generation mode for the compounds evaluated. It is common to use a base as a mobile phase pH modifier during mass spectrometry analysis in negative‐ion generation mode for acidic compounds; however, this approach is not always feasible in reversed‐phase LC separations. Strong organic acids will be fully ionized under basic conditions and they usually do not have good retention on the reversed‐phase column for adequate separation.…”
Section: Resultsmentioning
confidence: 99%
“…used alkali and alkaline earth acetates to form organometallics, and Curtis et al 9. and Attygalle et al 10. have demonstrated that metal oxalate anions, for example KC 2 O 4 − , dissociate upon collisional activation by successive losses of carbon dioxide, providing a useful method for making negatively charged atomic metal ions in the gas phase.…”
mentioning
confidence: 99%